Effects of Welding Parameter on Atom‐Scale Interfacial Diffusion Behavior of Al/Cu Dissimilar Friction Stir Welding. Issue 10 (26th July 2021) - Li, Qinghua; Dong, Zhibo; Ji, Shude; Yang, Laishan; Tao, Congcong; Zhou, Shouzhen; Hu, Guangxu
Abstract : The partial weak bonding phenomenon induced by an unsuitable welding parameter often occurs at the joint interface of Al/Cu dissimilar friction stir welding (FSW). Diffusion time, temperature, and pressure are the main factors that affect the diffusion behavior at the interface. Therefore, molecular dynamics (MD) simulation is used to investigate the influence mechanism of these factors from the perspectives of diffusion thickness, total energy, and volume. The diffusion time and the temperature affect the diffusion thickness significantly, whereas external pressure has little impact. The variations of total energy and volume consist of two stages, which are caused by the combined effects of lattice transformation and atomic diffusion. The variation processes of total energy and volume are accelerated with the increase in temperature due to a higher diffusion velocity, and it is delayed by external pressure at a higher temperature because the lattice transformation is inhibited. These findings are beneficial to the choice of welding parameters in actual production. Abstract : The influence mechanisms of diffusion time, temperature and pressure on aluminum/copper interfacial diffusion are investigated by molecular dynamics. The diffusion time and temperature affect diffusion thickness significantly, while pressure has little impact. The variation processes of total energy and volume consist of two stages which are accelerated with the increase of temperature and delayed by external pressure at higher temperature.